A systematic review of clinical practice guidelines and recommendations for the management of pain, sedation, delirium and iatrogenic withdrawal syndrome in pediatric intensive care - MacDonald, Ibo; Alvarado, Silvia; Marston, Mark T.; Gomez Tovar, Luz; Chanez, Vivianne; Favre, Eva; Gu, Ying; Trombert, Alexia; Perez, Maria-Helena; Ramelet, Anne-Sylvie (Frontiers in Pediatrics, 2023)
Introduction: This systematic review aimed to evaluate the quality of clinical practice guidelines (CPGs) and recommendations for managing pain, sedation, delirium, and iatrogenic withdrawal syndrome in pediatric intensive care. The objectives included evaluating the quality of recommendations, synthesizing recommendations, harmonizing the strength of the recommendation (SoR) and the certainty of evidence (CoE), and assessing the relevance of supporting evidence. This is a provisional file, not the final typeset article Methods: A comprehensive search in four electronic databases (Medline, Embase.com, CINAHL and JBI EBP Database), 9 guideline repositories, and 13 professional societies was conducted to identify CPGs published from January 2010 to the end of May 2023 in any language. The quality of CPGs and recommendations was assessed using the AGREE II and AGREE-REX instruments. Thematic analysis was used to synthesize recommendations, and the GRADE SoR and CoE harmonization method was used to interpret the credibility of summary recommendations.Results: A total of 18 CPGs and 170 recommendations were identified. Most CPGs were of mediumquality, and three were classified as high. A total of 30 summary recommendations were synthesized across each condition, focused on common management approaches. There was inconsistency in the SoRs and CoE for summary recommendations, those for assessment showed the highest consistency, the remaining were conditional, inconsistent, inconclusive, and lacked support from evidence.This systematic review provides an overview of the quality of CPGs for these four conditions in the PICU. While three CPGs achieved high-quality ratings, the overall findings reveal gaps, in the evidence base of recommendations, patient and family involvement, and resources for implementation. The findings highlight the need for more rigorous and evidence-based approaches in the development and reporting of CPGs to enhance their trustworthiness. Further research is necessary to enhance the quality of recommendations for this setting. The results of this review can provide a valuable foundation for future CPG development.